PERILAKU MORAL HAZARD (PERILAKU TIDAK JUJUR) PEDAGANG BERAS PASAR SETRAL PEKKABATA KABUPATEN POLEWALI MANDAR - Hasanuddin Hasanuddin; Juni Arsah Sukri; Ahmad Wijayanto; Heffi Christya Rahayu (ITB AAS Indonesia Surakarta, 2024)
The problem addressed in this study is whether there is moral hazard behaviortowards rice traders in the Pekkabata Central Market, Polewali Mandar Regency. This research is quantitative in nature, focusing on the analysis of moral hazard behavior among rice traders in the Pekkabata Central Market. The sample comprised 20 traders, and the sampling technique used was the sampling technique method. Data collection was conducted using Six Sigma, Editing, and Coding. Based on the research findings, it can be highlighted that the Pekkabata Central Market has advantages such as being a relatively large shopping center and easily accessible to the public. However, it also faces weaknesses, including a lack of traders who maintain honesty in their dealings with customers. The results of the research, based on the t-test, indicate that the variable of moral hazard behavior has a calculated value of 3.336, which is greater than the table value of 1.678. The significance value is 0.002, which is less than 0.05, indicating a positive relationship. This implies that the service variable significantly influences customer satisfaction